All scales matter - Bremer, Edith (2021)
Understanding extinction debt and how species are affected by landscape structure is important knowledge in order to form strategies for species protection in forestry and conservation. In this study, I investigate whether an extinction debt can be detected in two deadwood living lichen species by modelling their occurrence against past and present habitat amount in the landscape as well as amount of continuity forest (i.e. forests that never have been clearcut). A second objective was to assess the importance of landscape-scale characteristics compared to stand- and substrate characteristics for the occurrence of these species. I surveyed 55 stands in northern Sweden for occurrence of Hertelidea botryosa and Cladonia parasitica, as well as amount and characteristics of their deadwood substrate. From my results, I could neither confirm nor refute extinction debt in either species based on any landscape level effects. The species were decidedly more dependent on substrate characteristics, but also stand and landscape characteristics were important. The high dependency of these species on specific types of deadwood that are not easily recreated in a managed landscape indicates that the habitat amount in the landscape might be of greater importance than could be shown here as areas were classified as possible habitat based only on information about forest age and continuity without knowledge on the availability of the specific type of deadwood substrate. As the type of deadwood substrate preferred by the species is only created in specific stands and landscapes, and takes considerable amounts of time to produce, my results still underlines the importance for efforts in forest management to secure continuous supply of these deadwood qualities and to protect areas were such deadwood already exists.